Simbiose: relações mútuas através do fazer artístico - Alves, Don Gomes (2016)
The project "Symbiosis" aims to bring reflections on human beings and their relationship with the means they inhabit, whether for the environment, their habitat and/or other beings of our specie. In developing this search an experience was made in the Recycling Cooperative Healthy Environment (COOPERMAS), with activities and reflections that brought to light the prejudices surrounding that space, culminating in the use of art making how a relational tool among members and neighborhood working collective characteristics in a collaborative proposalIt was being built step by step. Human habits are put to debate this process and raise the power that cultural activities have to intervene in hostile environments, human working towards a connection between beings that circumscribe the cloth of Gaia.